Efeitos de carboidratos no desempenho, na digestão e no metabolismo de matrinxã (Brycon amazonicus) e híbridos de pintado (Pseudoplatystoma corruscans x Pseudoplatystoma fasciatum) em um período curto de alimentação - Camilo, Rodrigo Yamakami (2012)
Improvements in fish farming production require continuous research in nutrient formulation and diet technology. Feeding is the most important handling daily practiced by fish farmers and diets must supply the nutritional requirements to increase fish biomass. Aimed at improving the diets, a study was conducted to determine the ability of matrinxã (Brycon amazonicus) and of hybrid pintado (Pseudoplatistoma corruscans X Pseudoplatystoma fasciatum) to utilize different sources of carbohydrate in their diets. Triplicate groups of juveniles matrinxã were fed visual satiety one of five diets isonitrogenous (30% crude protein) and isolipidic (10% crude lipids) containing: 40% glucose, 40% maltose, 40% dextrin, 40% pregelatinized or 40% raw starch for 27 days. Weight gain, feed conversion ratio, feed consumption, digestive enzymes (amylase, maltase, unspecific proteases, trypsin, chymotrypsin, unspecific lipase and alkaline phosphatase), metabolites (glucose, lactate, pyruvate, ammonia, protein, fat acids, triglycerides, amino acids and glycogen) were measured. The same was done with juvenile hybrid, but the diet containing 30% crude protein, 10% crude lipids and 30% one of five carbohydrates. The matrinxã amylase and maltase activities were higher than those of pintado. In both species, fish fed diet containing glucose had the worst weight gain, feed conversion ratio and feed consumption, digestive enzymes (P < 0.05) among all groups. These results were followed by fish fed with diet containing maltose. Weight gain and feed conversion of matrinxã fed with diets containing pregelatinized starch or raw starch and of hybrid pintado fed with diet containing pregelatinized were higher than those of fish fed with the other carbohydrates. In intestinal of both species, amylase activity was higher in group fed with raw starch diets. In matrinxã, the activities of other digestive enzymes showed no significant changes. In pintado the highest maltase activity was observed in fish fed with pregelatinized. The alterations in plasmatic, muscular and hepatic metabolic intermediaries concentration become evident that the matrinxã and hybrid pintado were able to adapt its intermediary metabolism to the changes on the feeding condition to preserve vital functions.